A procurement policy-making pathway to future-proof large-scale transport infrastructure assets - Love, Peter; Ika, L.A.; Matthews, Jane; Li, Xinjian; Fang, W. (ELSEVIER SCI LTD, 2021)
Governments worldwide have made a significant financial commitment to combat increasing traffic congestion and ageing transport networks over the next decade. However, large-scale transport projects are often late, over-budget, and below quality, making it difficult to future-proof assets and accommodate unanticipated changes. Evidence indicates that the traditional procurement model for large-scale projects used by Australian State Governments, for example, fails to deliver expected benefits. Markedly, a focused policy-making pathway is absent, especially for future-proofing these complex projects. Hence, the need to move away from a prevailing ‘understand, reduce, respond’ to a more adequate ‘understand, embrace, adapt’ attitude towards complexity and uncertainty in project procurement. The enabling functions of asset management, digitization, delivery, and finance might help. However, little is known about how they can coalesce to form a policy-making pathway to provide governments value for money outcomes and ensure assets are future-proofed. In this paper, we fill this void by reviewing the normative literature and proposing a conceptual approach. The issues we examine are of the utmost interest to governments worldwide as they grapple with designing, constructing, operating and maintaining transport assets that are both resilient to unexpected events and adaptable to changing needs, uses or capacities including climate change.